2004
DOI: 10.1086/502371
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Carriage of Methicillin-ResistantStaphylococcus aureusAmong Hospital Staff and Outpatients

Abstract: This study sought to determine the rate of nasal methicillin-resistant Staphylococcus aureus (MRSA) carriage among hospital staff and outpatients. Nasal swabs were obtained from 500 outpatients and 500 hospital staff. Hospital staff were 2.3-fold more likely to carry MRSA than were outpatients (6% vs 2.6%, P = .013).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
3
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 19 publications
6
29
3
3
Order By: Relevance
“…Cokca have reported the rate of MRSA nasal carriage to be 6% among hospital personnel and 2.6% among outpatients [5] . In this study, MRSA nasal carriage rate was 6.12% among physicians, 6.57% among nurses, and 5.17% among auxiliary health personnel.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Cokca have reported the rate of MRSA nasal carriage to be 6% among hospital personnel and 2.6% among outpatients [5] . In this study, MRSA nasal carriage rate was 6.12% among physicians, 6.57% among nurses, and 5.17% among auxiliary health personnel.…”
Section: Discussionmentioning
confidence: 98%
“…S. aureus nasal carriage and MRSA nasal carriage rates in inpatients and outpatients in various studies are shown in Table 4. Risk factors for MRSA infection and colonization include recent admission to the hospital, surgical intervention, intravenous drug use, underlying disease, close contact with hospital personnel, antibiotic use in the last six months, institutionalization and the presence of hospital personnel among family members [5,8,11,16] . In our study, hospital personnel, inpatients and outpatients were evaluated for risk factors for MRSA nasal carriage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca S. aureus nazal taşıyıcı-lığı oranı kontakt dermatitli hastalar, hemodiyaliz ve periton diyalizi hastaları, HIV-pozitif hastalar, intravenöz uyuşturucu bağımlıları ve hastane personelinde normal popülasyondan daha yüksektir (12,16). Yine, çalışmalar diyabetik hastalarda normal popülasyona oranla S. aureus nazal taşıyıcılığının daha fazla olduğunu göstermiştir (17).…”
Section: İrdelemeunclassified
“…Stafilokok infeksiyonlarının epidemiyolojisinde nazal taşıyıcılığın önemi 40 yıldan daha uzun bir süredir bilinmektedir. Literatürde S. aureus nazal taşıyıcılığı ve infeksiyon arasındaki ilişkiyi bildiren ve nazal taşıyıcılığın eradikasyonunun infeksiyon riskini azaltabileceğini gösteren çalışmalar vardır (9)(10)(11)(12). Ancak DA yarası olan hastalarda S. aureus nazal taşıyıcılığı ve yara infeksiyonu arasın-daki olası ilişkiyi gösteren yeterince çalışma mevcut değildir (7,8).…”
Section: Introductionunclassified